Thermodynamic and kinetic cooperativity in ligand binding to multiple sites on a protein: Ca2+ activation of an ATP-driven Ca pump. - Tanford, C (1985)
Contrary to common belief, theoretical analysis does not predict any necessary relationship between cooperativity in the equilibrium binding of an ion to multiple binding sites on a protein and cooperativity in the kinetic activation of a reaction for which such binding is prerequisite. The sarcoplasmic reticulum Ca pump protein, for example, has two high-affinity binding sites for Ca2+, here considered to be nearly identical and independent. Equilibrium binding to these sites can be highly cooperative in spite of site-independence, as demonstrated by the well-known allosteric mechanism based on Wyman's principle of linked functions. We show in this paper that kinetic activation of the pump reaction cycle by binding of Ca2+ to these same sites can likewise be a cooperative function of Ca2+ concentration but that the criteria that determine cooperativity in the two situations are different. It is possible to observe kinetic cooperativity without concomitant cooperativity in equilibrium binding and vice versa. Application of these theoretical considerations to experimental data for the pump protein raises questions about the Ca2+ binding mechanism.